Alveolar bone grafting - Lilja Jan (Indian Journal of Plastic Surgery)
In patients with cleft lip and palate, bone grafting in the mixed dentition in the residual alveolar cleft has become a well-established procedure. The main advantages can be summarised as follows: stabilisation of the maxillary arch; facilitation of eruption of the canine and sometimes facilitation of the lateral incisor eruption; providing bony support to the teeth adjacent to the cleft; raising the alar base of the nose; facilitation of closure of an oro-nasal fistula; making it possible to insert a titanium fixture in the grafted site and to obtain favourable periodontal conditions of the teeth within and adjacent to the cleft. The timing of the ABG surgery take into consideration not only eruption of the canine but also that of the lateral incisor, if present. The best time for bone grafting surgery is when a thin shell of bone still covers the soon erupting lateral incisor or canine tooth close to the cleft.